Rhythmical organization, rhyme and sound harmony of Ukrainian paremias (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article the analysis of rhythmical pattern of Ukrainian paremias and peculiarities of their rhyme is accomplished; attention is paid to sound organization of proverbs, interaction of phonetical tools while creating an artistically perfect form. It helps to better memorize paremias in the process of communication.
Keywords: paremia; proverb; rhyme; rhythm; alliteration; assonance